A Rh(ii)-catalyzed three-component reaction of 3-diazooxindoles with N, N-disubstituted anilines and glyoxylates for the synthesis of 3-aryl-3-substituted oxindoles. Issue 43 (12th October 2016) - Jia, Shi-Kun; Song, Long-Long; Lei, Yu-Bing; Gopi Krishna Reddy, A.; Xing, Dong; Hu, Wen-Hao
Abstract : A Rh2 (OAc)4 catalyzed three-component reaction via aromatic C–H bond functionalization is developed for the synthesis of 3-aryl-3-substituted oxindole derivatives. Abstract : A simple and effective method for the synthesis of 3-aryl-3-substituted oxindole derivatives via a [Rh]-catalyzed three-component reaction of 3-diazooxindoles with N, N -disubstituted anilines and glyoxylates is developed. This transformation is proposed to proceed through an intermolecular aldol-type trapping of zwitterionic intermediates.